The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10278-014-9766-0
|View full text |Cite
|
Sign up to set email alerts
|

Staining Correction in Digital Pathology by Utilizing a Dye Amount Table

Abstract: The stained colors of the tissue components are popularly used as features for image analysis. However, variations in the staining condition of the histology slides prompt variations to the color distribution of the stained tissue samples which could impact the accuracy of the analysis. In this paper, we present a method to correct the staining condition of a histology image. In the method, a look-up table (LUT) based on the dye amounts absorbed by the sample is built. The LUT can be built when either (i) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In order to account for scanner-induced variations, Bautista et al (2014) proposed to use a colour-calibration slide made in-house to derive a colour correction matrix. Bautista and Yagi (2015) showed that it is possible to achieve consistent and accurate segmentations with simple classifiers by accounting for the staining conditions of the slides using dye amount tables.…”
Section: Preprocessing Of Digital Pathologymentioning
confidence: 99%
“…In order to account for scanner-induced variations, Bautista et al (2014) proposed to use a colour-calibration slide made in-house to derive a colour correction matrix. Bautista and Yagi (2015) showed that it is possible to achieve consistent and accurate segmentations with simple classifiers by accounting for the staining conditions of the slides using dye amount tables.…”
Section: Preprocessing Of Digital Pathologymentioning
confidence: 99%
“…Attention has been drawn to the importance of accurate color reproduction in WSI and steps to ensure or improve upon it. [ 78 96 ] However, it was not until relatively recently that pathology articles and textbooks were regularly printed in color and a portion of currently practicing pathologists trained, at least partially, with gray scale images as the norm. In addition, a few studies have been published on color blindness in pathologists.…”
Section: T He I Mpact Of D mentioning
confidence: 99%
“…As discussed in our previous study. Bautista et al [ 27 ] the staining condition can be controlled and standardized using spectral information instead of RGB data.…”
Section: Color Standardizationmentioning
confidence: 99%